2011
DOI: 10.1007/s10815-011-9563-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration of cryo-storage of mouse oocytes on cryo-survival, fertilization and embryonic development following vitrification

Abstract: Purpose To investigate the effects of cryo-storage duration in liquid nitrogen on oocyte cryo-survival, fertilization and embryonic development following vitrification and warming. Methods Mature mouse oocytes were vitrified with McGill Cryoleaf and stored in liquid nitrogen for a period of 8-10 days, 90-92 days and 180-182 days, respectively. After warming, the survived oocytes were inseminated by intracytoplasmic sperm injection (ICSI) and cultured for 120 h. The rates of oocyte cryo-survival, cleavage and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
(44 reference statements)
0
16
0
1
Order By: Relevance
“…Although it is generally assumed that thermally driven reactions do not occur in cells at À196°C, it has been reported that, in the case of radiation of an LN 2 /oxygen mixture, a synthesis of oxygen radicals resulting from ozone formation and decomposition cannot be excluded and is even enhanced by the catalytic effect of nitrogen. A recent publication reports that mouse oocytes show impaired survival, fertilization rates and embryonic development after prolonged contact with LN 2 (Yan et al, 2011). These findings are of special interest as the biological sample in the open devices commonly used is constantly exposed to LN 2 since the plug is inserted into the outer straw in the LN 2 bath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is generally assumed that thermally driven reactions do not occur in cells at À196°C, it has been reported that, in the case of radiation of an LN 2 /oxygen mixture, a synthesis of oxygen radicals resulting from ozone formation and decomposition cannot be excluded and is even enhanced by the catalytic effect of nitrogen. A recent publication reports that mouse oocytes show impaired survival, fertilization rates and embryonic development after prolonged contact with LN 2 (Yan et al, 2011). These findings are of special interest as the biological sample in the open devices commonly used is constantly exposed to LN 2 since the plug is inserted into the outer straw in the LN 2 bath.…”
Section: Discussionmentioning
confidence: 99%
“…the constant exposure to toxic low-molecular-weight compounds, still remain if the devices are not hermetically closed (Yan et al, 2011). Although the probability of contamination in LN 2 is still being discussed, this risk is important and indicates that the storage system, especially for long-term storage conditions, should be revised.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly admitted in the field of thermodynamic cryobiology that once the glass is formed, it can be aged. 40.0 versus 38.5% after 6 years: NS). In addition, no increase in the malformation rate over time was observed.…”
Section: Closed Systemmentioning
confidence: 87%
“…Although, it is generally assumed that thermally driven reactions do not occur in cells at -196°C, it has been reported that in the case of radiation of an LN 2 /oxygen mixture a synthesis of oxygen radicals resulting from ozone formation and decomposition cannot be excluded and is even enhanced by the catalytic effect of nitrogen. Mouse oocytes show impaired survival, fertilization rates and embryonic development after prolonged contact with LN 2 (40). (3,7,9,26,43).…”
Section: Open Systemmentioning
confidence: 99%
“…Hence, alternative methods for crypreservation of hESC were explored. The vitrification technique is for long in use for cryopreservation of embryos and ooctyes in veterinary and human application (Yan et al, 2011). Vitrification represents the direct transformation of a substance into a glass like state without the formation of ice crystals (M. Ojovan, n d).…”
Section: Cryopreservation Of Non-hematologic Stem Cellsmentioning
confidence: 99%